A phage-displayed nanobody-based competitive immunoassay for the detection of African swine fever virus antibodies - Wenting Chen; Jifei Yang; Qingli Niu; Jinming Wang; Yanghe Liu; Xuesai Li; Yaru Zhao; Zhonghui Zhang; Zhijie Liu; Guiquan Guan; Hong Yin (Virology Journal)
Abstract African swine fever (ASF) is a highly infectious and devastating disease that poses a significant threat to the global swine industry. The rapid spread of ASF and its ongoing pandemics continue to impact pig farming worldwide. The absence of an effective vaccine, coupled with the complexity of the African swine fever virus (ASFV), makes the control and eradication of ASF a formidable challenge. Nanobodies, derived from camelids, have emerged as promising alternatives to conventional monoclonal antibodies, offering distinct advantages in various biological applications. In this study, specific nanobodies targeting the ASFV K205R protein were selected from a phage-displayed immune library. Ten individual nanobodies were isolated based on their complementary determining regions (CDRs), and four were found to bind to the naive K205R protein of ASFV. After evaluation, nanobody VHH1 was selected for the development of a competitive enzyme-linked immunosorbent assay (ELISA) for ASFV antibody detection. The assay was optimized for various reaction conditions, and the cut-off value was determined to be 26.85%, with diagnostic sensitivity and specificity of 97.52% and 97.48%, respectively. No cross-reactivity was observed with sera from pigs infected with other swine viruses, and the assay exhibited a detection sensitivity of 1:128. Comparative analysis of clinical samples showed a high concordance rate (98.98%) between the nanobody-based and monoclonal antibody-based ELISAs (Mab-cELISA). In conclusion, this study presents a phage-displayed nanobody-based competitive ELISA for the detection of ASFV antibodies, which could be valuable for ASF sero-surveillance. Additionally, the K205R-specific nanobodies identified here may be adapted for other biological or biomedical applications.